The binding of a c-MYC promoter G-quadruplex to neurotransmitters: An analysis of G-quadruplex stabilization using DNA melting, fluorescence spectroscopy, surface-enhanced Raman scattering and molecular docking - Andregic, Nicole; Weaver, Caitlin; Basu, Swarna (Biochimica et biophysica acta. General subjects, 2023)
The interactions of several neurotransmitter and neural hormone molecules with the c-MYC G-quadruplex DNA sequence were analyzed using a combination of spectroscopic and computational techniques. The interactions between indole, catecholamine, and amino acid neurotransmitters and DNA sequences could potentially add to the understanding of the role of G-quadruplex structures play in various diseases. Also, the interaction of the DNA sequence derived from the nuclear hypersensitivity element (NHE) III1 region of c-MYC oncogene (Pu22), 5'-TGAGGGTGGGTAGGGTGGGTAA-3', has added significance in that these molecules may promote or inhibit the formation of G-quadruplex DNA which could lead to the development of promising drugs for anticancer therapy. The results showed that these molecules did not disrupt G-quadruplex formation even in the absence of quadruplex-stabilizing cations. There was also evidence of concentration-dependent binding and high binding affinities based on the Stern-Volmer model, and thermodynamically favorable interactions in the form of hydrogen-bonding and interactions involving the π system of the aromatic neurotransmitters.The interactions of several neurotransmitter and neural hormone molecules with the c-MYC G-quadruplex DNA sequence were analyzed using a combination of spectroscopic and computational techniques. The interactions between indole, catecholamine, and amino acid neurotransmitters and DNA sequences could potentially add to the understanding of the role of G-quadruplex structures play in various diseases. Also, the interaction of the DNA sequence derived from the nuclear hypersensitivity element (NHE) III1 region of c-MYC oncogene (Pu22), 5'-TGAGGGTGGGTAGGGTGGGTAA-3', has added significance in that these molecules may promote or inhibit the formation of G-quadruplex DNA which could lead to the development of promising drugs for anticancer therapy. The results showed that these molecules did not disrupt G-quadruplex formation even in the absence of quadruplex-stabilizing cations. There was also evidence of concentration-dependent binding and high binding affinities based on the Stern-Volmer model, and thermodynamically favorable interactions in the form of hydrogen-bonding and interactions involving the π system of the aromatic neurotransmitters.